Pedagogy and Diversity: Difference or Deficit. (January 2022) - Sarangapani, Padma M.
Schools—their curriculum and pedagogy—assume the middle-class child as the norm, effectively rendering other childhoods and life-worlds as being deficient. Shifting away from this assumption, and acknowledging diversity, is usually understood as requiring an 'attitudinal' shift on the part of teachers. Teachers are usually held 'guilty' of having negative attitudes towards children of the poor. Explanations for the pedagogy generally then refer to these attitudes, and 'corrective action' then attends to an attitudinal change. The idea of 'multiple childhoods' is gaining influence in the teacher education curricula as providing an alternative normative framework that can enable teachers to work with, and retain, diversity. Some recent research into the manifestation of 'difference' in the primary school classroom indicates that differences are experienced by teachers as learning difficulty issues that need a curricular and pedagogic response. The child's home culture, home support for schooling and home socialization seem to enter into the pedagogy in more ways than can be addressed by changing the 'teachers' attitudes'. 'Educability' is a central (folk) concept for teachers who engage with and try to address the learning requirements of children, particularly those from underprivileged backgrounds (and particularly social classes lower than themselves). Four studies on teachers' experiences of 'difference' are drawn upon to engage with and to evolve an understanding of the specific implications of for pedagogy and educational aims.